2017
DOI: 10.1016/j.circir.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Rotura esplénica secundaria a absceso, causa poco común de neumoperitoneo. Reporte de un caso

Abstract: At presence of free air inside the abdominal cavity, is usually to think of a complicated diverticular disease, intestinal perforation or perforated peptic ulcer. The actual medical literature described very few cases of splenic abscess with pneumoperitoneum as cardinal manifestation. In our case, the splenic abscess was detected during exploratory laparotomy and only in retrospective the imaging studies were interpreted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The results of either blood or splenic abscess culture were as follows in reported cases: Positive for Klebsiella pneumoniae and anaerobe Prevotella intermedia in pus culture from the splenic abscess [3] , positive pus culture for Enterobacter cloacae [6] , positive pus culture for b-hemolytic Streptococcus, Escherichia coli ( E coli ), Morganella morganii , and Proteus mirabilis from the perisplenic fluid and positive blood culture for b-hemolytic Streptococcus [7] , positive abscess culture for Prevotella intermedia [8] , negative blood cultures for any growth of bacteria [9] , positive pus culture from abscess for E coli and negative blood culture [4] , positive abscess aspirate culture for peptostreptococcus species [10] , positive pus culture for E coli [11] . In addition, the spleen histopathology revealed infiltration of a moderate quantity of Gram-positive bacteria in 1 patient [12] and in 1 case, there was not any data regarding microbial culture [5] . As it is evident from these aforementioned findings, there was no dominant bacterial family or species, but it seems there is a little more proclivity for E coli and Prevotella intermedia to be the cause of splenic abscess which could become complicated by pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The results of either blood or splenic abscess culture were as follows in reported cases: Positive for Klebsiella pneumoniae and anaerobe Prevotella intermedia in pus culture from the splenic abscess [3] , positive pus culture for Enterobacter cloacae [6] , positive pus culture for b-hemolytic Streptococcus, Escherichia coli ( E coli ), Morganella morganii , and Proteus mirabilis from the perisplenic fluid and positive blood culture for b-hemolytic Streptococcus [7] , positive abscess culture for Prevotella intermedia [8] , negative blood cultures for any growth of bacteria [9] , positive pus culture from abscess for E coli and negative blood culture [4] , positive abscess aspirate culture for peptostreptococcus species [10] , positive pus culture for E coli [11] . In addition, the spleen histopathology revealed infiltration of a moderate quantity of Gram-positive bacteria in 1 patient [12] and in 1 case, there was not any data regarding microbial culture [5] . As it is evident from these aforementioned findings, there was no dominant bacterial family or species, but it seems there is a little more proclivity for E coli and Prevotella intermedia to be the cause of splenic abscess which could become complicated by pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 90%
“…We presented a case that was afflicted by a splenic abscess whose rupture led to pneumoperitoneum. Based on a comprehensive review of the literature, we found only 10 case reports illustrating pneumoperitoneum following the rupture of a splenic abscess [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] . The search strategy used for the purpose of discovering these articles was the utilization of the keywords "Splenic Abscess" AND "Pneumoperitoneum" in the databases of PubMed, Scopus, and Google Scholar Advanced Search.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Splenic abscesses commonly occur in the patients with hematologic disorders, diabetes, endocarditis, acquired immunodeficiency syndrome (AIDS), and urogenital infections [2]. Traditionally, antibiotics and splenectomy were considered as the treatment of choice.…”
Section: Introductionmentioning
confidence: 99%